2021
DOI: 10.21203/rs.3.rs-533888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID19 Vaccine Intentions in South Africa: Health Communication Strategy to Address Vaccine Hesitancy

Abstract: Background: Widespread vaccine acceptance is key to achieving herd immunity through vaccination against COVID19, especially because the available vaccines do not have 100% efficacy. The continued infection amongst the unvaccinated can lead to heightened risk of further virus mutation, exposing even those vaccinated to new virus strains. Therefore, there are social benefits in minimising vaccine hesitancy. The objective of this study is to assess the level of COVID19 vaccine hesitancy in South Africa, identify … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
7
1
1
Order By: Relevance
“…When contrasting with other regions, the prevalence of VI found in our study was relatively higher or similar to that found in some studies conducted in European and Asian countries such as Italy (ranging from 40.1% to 78.5%) [ 42 , 43 ], France (ranging from 30.5% to 77.6%) [ 44 , 45 ], Greece (ranging from 62% to 84.8%) [ 46 , 47 ], Germany (ranging from 58% to 70%) [ 48 , 49 ], UK (ranging from 64% to 73.5%) [ 50 , 51 ], China (ranging from 28.7% to 82%) [ 52 , 53 ], or Bangladesh (ranging from 26% to 65.5%) [ 54 , 55 ]. Likewise, South Africa reported a VI lower than our estimate for LAC [ 56 ]. [ 52 ] Nevertheless, these prevalences ranged broadly between different studies conducted in the same country or region [ 57 ].…”
Section: Discussioncontrasting
confidence: 54%
“…When contrasting with other regions, the prevalence of VI found in our study was relatively higher or similar to that found in some studies conducted in European and Asian countries such as Italy (ranging from 40.1% to 78.5%) [ 42 , 43 ], France (ranging from 30.5% to 77.6%) [ 44 , 45 ], Greece (ranging from 62% to 84.8%) [ 46 , 47 ], Germany (ranging from 58% to 70%) [ 48 , 49 ], UK (ranging from 64% to 73.5%) [ 50 , 51 ], China (ranging from 28.7% to 82%) [ 52 , 53 ], or Bangladesh (ranging from 26% to 65.5%) [ 54 , 55 ]. Likewise, South Africa reported a VI lower than our estimate for LAC [ 56 ]. [ 52 ] Nevertheless, these prevalences ranged broadly between different studies conducted in the same country or region [ 57 ].…”
Section: Discussioncontrasting
confidence: 54%
“…In agreement with this finding, Carrieri et al 2021 synthesized a machine-learning model for vaccine hesitancy among Italian municipalities' inhabitants, which indicated that socioeconomic indicators, e.g., the proportion of waste recycling and the employment rate, were the most powerful predictors of vaccine hesitancy at an area-level [69]. The household income was found to be a significant determinant for COVID-19 vaccine hesitancy among South African, Italian, and Portuguese adult populations during the pre-vaccination stage and the early stages of mass vaccination [70][71][72]. In a recent cross-sectional study, the lack of financial resources needed for health insurance was a trigger for COVID-19 vaccine hesitancy among US adults, thus emphasizing the role of a functional universal health coverage system in each country in the world, regardless of its economic level, to enhance the public's vaccination willingness [73].…”
Section: Discussionmentioning
confidence: 93%
“…Fifty-eight articles reported on acceptance, with acceptance percentages of COVID-19 vaccine ranging from 15.4% 52 to 90%. 31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80]…”
Section: Resultsmentioning
confidence: 99%
“…31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80][81][82] Of 58 studies, 31 reported factors that influence the desire to be vaccinated and were grouped as ...…”
Section: Resultsmentioning
confidence: 99%